2010
DOI: 10.1177/1079063210369013
|View full text |Cite
|
Sign up to set email alerts
|

Contact Sexual Offending by Men With Online Sexual Offenses

Abstract: There is much concern about the likelihood that online sexual offenders (particularly online child pornography offenders) have either committed or will commit offline sexual offenses involving contact with a victim. This study addresses this question in two meta-analyses: the first examined the contact sexual offense histories of online offenders, whereas the second examined the recidivism rates from follow-up studies of online offenders. The first meta-analysis found that approximately 1 in 8 online offenders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
194
3
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(221 citation statements)
references
References 31 publications
16
194
3
8
Order By: Relevance
“…The results support growing research that suggests CSEMOs may be a distinct group of sex offenders, in relation to their cognitions, and could support the hypothesis that there may be differing typologies of CSEMOs Seto et al, 2011). The diverse range of themes captures the complexity and heterogeneity of the cognitions in CSEMOs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results support growing research that suggests CSEMOs may be a distinct group of sex offenders, in relation to their cognitions, and could support the hypothesis that there may be differing typologies of CSEMOs Seto et al, 2011). The diverse range of themes captures the complexity and heterogeneity of the cognitions in CSEMOs.…”
Section: Discussionsupporting
confidence: 75%
“…A substantial rise in convictions for CSEM-related offences (Radford et al, 2011) has consequently resulted in an increase in research on CSEMOs (Babchishin, Hanson, & Hermann, 2011;Babchishin, Hanson & VanZuylen, 2015;Seto, Hanson, & Babchishin, 2011). One of the most widely researched questions is whether CSEMOs are a distinct type of sex offender from contact sex offenders (CSOs) and comparison studies have identified some differences regarding psychological and offence-related variables Elliott, Beech, & Mandeville-Norden, 2012;Lee, Li, Lamade, Schuler, & Prentky, 2012;McCarthy, 2010).…”
Section: The Emergence Of Non-contact Sex Offending As a Research Areamentioning
confidence: 99%
“…), which reduced to 13.3% when self-report data was excluded. A year later, with an increased sample of 4,697 online offenders, Seto, Hanson, and Babchishin (2010) identified 17.3% of offenders with a historic contact sex offence, ''mostly against a child'' (p. 9), or 12.2% when only official information was included. Seto and his colleagues also examined the recidivism rates of a combined sample of 2,630 online offenders.…”
Section: Child Pornography Offending and Contact Sexual Abusementioning
confidence: 99%
“…Ainsi, il est important de noter que les études scientifiques semblent indiquer que seul un faible pourcentage des consommateurs de pornographie juvénile ont également commis des agressions sexuelles (p. ex. : Seto, Hanson et Babchishin, 2011). Ces études laissent plutôt entendre que la majorité des auteurs de délits pédopornographiques possèdent des caractéristiques psychologiques et sociales qui les protègent d'un passage à l'acte avec contact (voir Finkelhor, 1984).…”
Section: Implications De L'étudeunclassified
“…Bien que seulement une faible portion des cyberdélinquants sexuels franchisse cette barrière (voir Seto et al, 2011), il existe des scripts observables qui expliquent comment ce processus s'opère. Ces scénarios se distinguent tous par une volonté d'interagir non plus avec d'autres collectionneurs, mais bien d'entrer directement en contact avec l'objet même de la collection, soit l'enfant.…”
Section: Le Script Du Distributeurunclassified